A study on the influence of community spiritual comfort service on the mental health of older people - Dai, Jing; Liu, Yang; Zhang, Xue; Wang, Zongyue; Yang, Yunjuan (Frontiers in Public Health, 2023)
Background: China is experiencing rapid population aging, with the proportion of elderly people aged 60 and above reaching 19.8% of the total population in 2022. With the growth of age, the physical function of older adults declines and their mental health is getting worse, with the increasing trend of empty nesting and childlessness, older adults lack information and social interaction with others and fall into social isolation, loneliness and some mental health problems, the proportion of older adults with mental health problems gradually rises, requiring effective ways to intervene in the mental health of older adults and promote healthy aging. Aim of the study: The present study investigated the influence of spiritual comfort elderly services on the mental health of 12,624 older adults aged 60 years or older in 23 provinces in China from 2017 to 2018, with the aim of providing a case for the development of more targeted mental health strategies for older people. Methods: Using the data from the 2018 CLHLS Survey, the influencing factors of the mental health of older people were analyzed using chi-square test and the logit regression model. The mechanism of the health care facilities and the spiritual comfort services on mental health was analyzed using the chain mediation effect. Results: The spiritual comfort services decreased the risk of negative emotion and mental health of older adults, with female (OR=1.168), rural residents (OR=1.385), no drinking (OR=1.255), not exercising (OR=1.543), not having pension insurance (OR=1.233), and low annual household income (OR=1.416) being the characteristics as risk factors. The mediating effect results showed that the health care facilities had a partial mediating effect between the spiritual comfort services and the mental health status of older people, and the mediating effect accounted for 40.16% of the total effect. Conclusions: The use of spiritual comfort services can effectively reduce and alleviate the adverse mental health symptoms of older people, promote guidance and health education for healthy older people and chronically ill patients, and improve the good health perception of older people in order to improve their quality of life and mental health status.